Implementing High-Intensity Interval Training in Physical Education: Effects on Adolescents’ Exercise Motivation - Petar Mitić; Rade Jovanović; Nenad Stojiljković; Nebojša Trajković; Mihai Olanescu; Adrian Suciu; Danut Popa; Miruna Peris (Behavioral Sciences)
(1) Background: The aim of this study was to determine the effects of high-intensity interval training (HIIT) implemented in physical education classes on adolescents’ motivation for exercise. (2) Methods: This study involved 60 male adolescents (16.23 ± 0.6 years) recruited from a local high school who were randomly assigned to either the HIIT group or the control group (CG). The Exercise Motivation Inventory-2 (EMI-2) questionnaire was used to assess how participation in a HIIT program influenced the motivation to exercise among adolescents. The experimental program consisted of a 12-week HIIT program, integrated into the preparatory part of physical education classes. Sessions were held twice weekly, with each session lasting ~10 min. The HIIT group performed the Tabata protocol, which consisted of two 4 min sequences of eight different high-intensity exercises (burpees, split jumps, jumping jacks, push-ups, wall ball, crunches, frog jumps, and Russian twists), each lasting 20 s with 10 s rest intervals, separated by a 1 min recovery period. The control group conducted the traditional moderate-intensity warm-up exercises for the same total duration. After the warm-up protocols, both groups continued with the same physical education classes, which included a variety of instructional and moderate-intensity activities. (3) Results: A significant time × group interaction was observed for social recognition (p = 0.04; partial eta squared η2p = 0.079, medium effect), indicating that HIIT had a superior effect compared to CG. Affiliation also showed a significant improvement in the HIIT group (p = 0.02), while no significant changes were noted in the CG (p = 0.35). Similarly, competition significantly increased in the HIIT group (p = 0.02), whereas no significant differences were found in the CG (p = 0.74). For all other motivational factors, no significant effects of time or group factors were found (p > 0.05). (4) Conclusions: This study highlights the positive effects of school-based HIIT on male adolescents’ motivation, particularly in the area of social recognition.